Environmental determinants for participation among stroke survivors in Africa, a scoping review - Assefa, Yohannes Awoke; Demeke, Zelalem Dessalegn; Wolde, Sara; Guadie, Yisak Girma (Frontiers in Rehabilitation Sciences, 2023)
Purpose In this review, we aimed to review the environmental factors that are influencing the participation of stroke survivors in Africa. Methods: Four electronic databases were systematically searched in August 2021, and identified articles were screened by two authors based on predetermined criteria. No date restrictions were imposed, and we included any type of paper, including grey literature. We followed the scoping review framework by Arksey and O'Malley (1), later revised by Levac, Colquhoun (2). The whole finding is reported using PRISMA-ScR. Results: 584 articles were generated by the systematic search, and one article was added manually. After removing duplicates, the title and abstract of 498 articles were screened. From the screening, 51 articles were selected for full article review, from which 13 met the criteria to be included. In total, 13 articles were reviewed and analyzed based on the International Classification of Functioning, Disability and Health (ICF) framework of the environmental determinants. Products and Technology, Natural Environment and Human-Made Changes to Environment, and Services, Systems and Policies found to be a barrier for stroke survivors to participate. Conversely, stroke survivors are getting good support from their immediate family and health professionals. Conclusion: This scoping review sought to identify the environmental barriers and the facilitators that are determining the participation of stroke survivors who are living in Africa. The results of this study can serve as a valuable resource for policymakers, urban planners, healthcare professionals, and other stakeholders involved in disability and rehabilitation. Nonetheless, additional research is necessary to validate the identified facilitators and barriers.